PENGARUH LINGKUNGAN KERJA DAN RELIGIUSITAS TERHADAP KINERJA PEGAWAI PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA MUARO JAMBI - Surni Nurlita; Usdeldi; Nurfitri Martaliah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to reveal the influence of work environment and religiosity on the performance of employees of Perumda Air Minum Tirta Muaro Jambi. This thesis uses a quantitative approach using multiple regression statistical analysis methods partially and simultaneously. The results of the study indicate that the independent variable Work Environment with a calculated t value on the Work Environment variable (X1) is 3.151 with a significance level of 0.000. Because the calculated t value is greater than the t table, namely (3.151> 1.307) and a significance value of 0.003 <0.05, Ho is rejected and Ha is accepted. So the Work Environment variable (X1) has an influence on the performance of employees of Perumda Air Minum Tirta Muaro Jambi partially. The independent variable of religiosity is obtained that the calculated t value on the religiosity variable (X2) is 12.272 with a significance level of 0.000. Because the calculated t value is greater than the t table, namely (12.272> 1.307) and the significance value is 0.000 <0.05, then Ho is rejected and Ha is accepted. So the religiosity variable (X2) has an influence on the performance of Perumda Air Minum Tirta Muaro Jambi employees partially. Based on the calculated F value (215.067)> F table (4.13) and the significant value (0.000) <a (0.05), it is concluded that Ho is rejected and Ha is accepted, meaning that the work environment and religiosity together or simultaneously influence the performance of Perumda Air Minum Tirta Muaro Jambi employees.